Standardizing Administrative Sufficiency Scale For Scouting Leaders With Wood Badge In The Iraqi General Directorate of Education - Jabar, Haider; Nabhan, Nada (Journal of Physical Education, 2019)
Standardizing the wood badge for scouting leaders administrative sufficiency scale is considered a new project and it aimed at developing scouts and encouraging them to participate more in the educational community. Standardizing administrative scale is part of developing and process that has a great role in improving scouting leaders. Scouting leaders are the fundamental pillar for all educational and scouting institutes.